A Mini Review on Pyrolysis of Natural Algae for Bio-Fuel and Chemicals - Wei Xu (MDPI AG, 2021)
The disposal and use of natural algae have recently been the subject of great interest, due to increasing concern for environmental protection and resource utilization. In this paper, a mini review of recent research on the pyrolysis of natural algae, especially the algae from water blooms, is presented. The chemical compositions of the natural algae are summarized, and the pyrolysis properties of different compositions are reviewed. Non-catalytic, catalytic, and integrated catalytic processes are reviewed. Different ideas and methods for the production of bio-fuel or chemicals are discussed. Apparently, deoxygenation and denitrogenation are highly necessary for algae-based bio-fuel and catalysts play an important role in these processes. In addition, the integrated catalytic process, which involves catalysis and other operation conditions aside from the thermal treatment under inert atmosphere, shows potential for the valorization of algae-based bio-oil. Based on the recent concept and progress, the research gaps are discussed, followed by the challenges and proposals to achieve high-value utilization of the natural algae.